(untitled) (World Economics and Finance Bulletin, 2026)
This article analyzes the significance, essence, and implementation mechanisms of innovative approaches in the development of teachers’ professional competencies. It also highlights the issues of enhancing teachers’ professional potential through the effective use of modern pedagogical technologies, interactive methods, and digital tools in the educational process. Based on the competency-based approach, the article systematically substantiates innovative methods aimed at developing teachers’ knowledge, skills, and competencies. The findings of the study are of significant importance for ensuring teachers’ professional development, improving the quality of education, and forming a modern educational environment